MXene-CMC composite membrane for salinity difference energy collection and preparation method of MXene-CMC composite membrane
By preparing the MXene-CMC composite membrane, the problems of low power density and insufficient mechanical strength in the prior art are solved, and efficient and economical salt energy collection and acid-base wastewater treatment are achieved.
Patent Information
- Application Number
- CN202411882094.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The prior art is used on a macroscopic scale for salt differential energy collection, with power density below the minimum standard for commercial profits and insufficient mechanical strength.
Using MXene-CMC composite membrane, a composite membrane with high surface charge density and mechanical strength was prepared by preparing MXene solution and CMC solution, combined with electromagnetic stirring and vacuum-assisted suction filtration technology.
A high power density salt-difference energy collection is achieved, with output power density up to 17.10 W/m² to 53.78 W/m² and 200 W/m² under acid and alkali conditions, and at a cost lower than that of pure MXene membranes.
Smart Images

Figure CN119656875A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of development of ocean salinity difference energy, relates to a MXene-CMC composite membrane for collecting salinity difference energy, and further relates to a method for preparing the MXene-CMC composite membrane for collecting salinity difference energy. Background Art
[0002] In recent years, with the rapid growth of global energy demand, the attention paid to salinity difference energy has increased significantly. It is calculated that the free energy change caused by the mixing of seawater and river water can reach 2.72 kJ / L, that is, every cubic meter of river water flowing into the ocean can generate about 0.8kWh of energy, which is equivalent to the energy released by water falling from a 280-meter-high dam. The global potential of this energy cannot be underestimated. In addition, in the process of treating industrial wastewater, the energy that is often overlooked is actually a considerable blue energy. It is reported that the total amount of blue energy in the world is as high as 30 terawatts (TW), of which the theoretically available resources are about 2.4 to 2.6 TW, which is equivalent to the power generation capacity of more than 100 Three Gorges power stations, making it the second largest ocean energy after wave energy. Therefore, the effective collection and utilization of ocean salinity difference energy is expected to alleviate the current energy shortage problem to a large extent.
[0003] The core component of the salt difference energy collection device based on RED technology is the selective ion exchange membrane. The device is driven by the salt concentration difference, selectively passing ions of specific electrical properties through the ion exchange membrane, thereby forming a potential difference, and directly converting the salt difference energy into electrical energy. In recent years, two-dimensional materials such as graphene, graphene oxide (GO), boron nitride (BN), carbon nanotubes and transition metal disulfides (TMDs) have attracted widespread attention in the research of salt difference power generation. Due to their excellent electrical properties, these materials can achieve power densities from several kW / m² to an astonishing 1000 kW / m² in a microscopic measurement area. However, when the effective test area is extended to the macroscopic scale, the concentration polarization phenomenon causes the ion flux of the porous membrane to be significantly lower than the theoretical value of the sum of single holes, resulting in a sharp drop in power density. At present, the salt difference power collection performance of materials such as molybdenum disulfide, GO and MXene is relatively outstanding, but it is still lower than the minimum standard for achieving commercial profitability (5 W / m²), and its mechanical strength is low.
[0004] Sodium carboxymethyl cellulose (CMC) is an important water-soluble polysaccharide widely used in food, medicine and industry. Due to its unique properties, the development and application of CMC can help improve the performance and quality of various products. However, there are relatively few studies on CMC in osmotic energy capture. In fact, the carboxyl groups (-COOH) introduced into CMC during the modification process of natural cellulose make it negatively charged in solution, while the hydroxyl groups (-OH) in the original cellulose are still retained. Therefore, the CMC molecular chain can be connected with some nanosheets (such as MXene containing functional groups such as -F, -O- and -OH) through hydrogen bonds, thereby improving the surface charge and mechanical strength of the membrane, making it have potential application value in high-performance osmotic energy extraction. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a MXene-CMC composite membrane for salt difference energy collection, wherein the composite membrane prepared by the method has the characteristics of high power density, good stability and high economic value.
[0006] Another object of the present invention is to provide a MXene-CMC composite membrane for salinity energy collection.
[0007] The first technical solution adopted by the present invention is a method for preparing a MXene-CMC composite membrane for collecting salinity difference energy, which specifically comprises the following steps: Step 1, preparing MXene solution; Step 2, preparing CMC solution; Step 3, placing the MXene solution prepared in step 1 into the CMC solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a suction filtration bottle, taking the mixed dispersion in the suction filtration bottle for vacuum-assisted filtration, and obtaining a polycarbonate membrane covered with a MXene-CMC composite membrane; Step 5: Peel off the MXene-CMC composite membrane from the polycarbonate membrane in the polycarbonate membrane covered with the MXene-CMC composite membrane, filter the water, and obtain a MXene-CMC composite membrane for collecting salt difference energy.
[0008] The first technical solution of the present invention is also characterized in that: The specific process of step 1 is: taking a quantitative MXene dispersion into a reactor, performing ultrasonic treatment, and obtaining a MXene solution.
[0009] The concentration of MXene solution is 1-5 mg / mL.
[0010] The ultrasonic treatment time is 4-6 min.
[0011] The specific process of step 2 is: Step 2.1, take deionized water into the reactor and take a certain amount of CMC solid powder; Step 2.2: Dissolve CMC solid powder in deionized water and fully dissolve it by electromagnetic stirring to obtain a CMC solution.
[0012] The concentration of CMC solution is 2-10 mg / mL.
[0013] The electromagnetic stirring time is 24-36h.
[0014] In step 3, the electromagnetic stirring is performed using an electromagnetic stirrer, the rotation speed of the electromagnetic stirring is 1000-1500 rpm, and the time of the electromagnetic stirring is 12-24h.
[0015] The time of vacuum-assisted filtration in step 4 is 3-7 days.
[0016] The second technical solution adopted by the present invention is that the MXene-CMC composite membrane for salt difference energy collection is prepared by the preparation method of the MXene-CMC composite membrane for salt difference energy collection.
[0017] The beneficial effects of the present invention are as follows: The present invention provides a MXene-CMC composite membrane for salt difference energy collection and a preparation method. Sodium carboxymethyl cellulose (CMC) is selected as a connector between MXene nanosheets and enhances the surface charge of each nanosheet. Compared with pure MXene membranes, the composite membranes exhibit higher surface charge density and mechanical strength. Under the conditions of simulated river water and real seawater mixing, the output power density of the composite membrane can reach 17.10 W / m², and under the conditions of simulated river water and salt lakes, this value increases to 53.78 W / m². Experimental and simulation results show that the increase in the radial size and surface charge of the nanocomposite membrane channel is the key factor in achieving high output power. In addition, the MXene-CMC composite membrane is also used to extract osmotic energy from pH gradients, H + The high diffusion rate and neutralization reaction of the membrane make the output power density as high as 200 W / m² under acid-base conditions. It is worth noting that the economic efficiency of the membrane is a major challenge for the industrial application of osmotic energy collection. In the MXene-CMC composite membrane prepared in this application, the more expensive MXene (Ti 3 C 2 Tx) only serves as a framework, while environmentally friendly and inexpensive sodium carboxymethyl cellulose is the dominant material. The composite membrane is significantly lower in cost than pure MXene membrane, while its energy collection performance far exceeds its performance, thus meeting the economic requirements well. This provides a new idea for designing high-performance and inexpensive nanomembranes to extract osmotic energy and treat acidic and alkaline wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic flow chart of a method for preparing a MXene-CMC composite membrane for collecting salinity difference energy according to the present invention; Figure 2 is a molecular structural formula diagram of CMC in Example 6 of the present invention; Figure 3 is a schematic diagram of a MXene nanosheet in Example 6 of the present invention; Figure 4 is a physical picture of the MXene-CMC composite membrane in Example 6 of the present invention; Figure 5 is a schematic cross-sectional view of the MXene-CMC composite membrane in Example 6 of the present invention; Figure 6 is a surface SEM image of the pure MXene film in Example 6 of the present invention; Figure 7 is a surface SEM image of the MXene-CMC composite film in Example 6 of the present invention; Figure 8 is a cross-sectional SEM image of the pure MXene film in Example 6 of the present invention; Fig. 9 is a cross-sectional SEM image of the MXene-CMC composite film in Example 6 of the present invention; Fig.10 is a stress-strain curve diagram of the MXene-CMC composite film in Example 6 of the present invention; Fig.11 is a schematic diagram of the contact angle of the MXene-CMC composite film in Example 6 of the present invention; Fig.12 is the XRD spectra of the pure MXene film and the composite film in Example 6 of the present invention; Fig.13 is a zeta potential diagram of the dispersions with different blending ratios in Example 6 of the present invention; Fig.14 is the XPS spectrum of the MXene-CMC composite film in Example 6 of the present invention; Fig.15 is a schematic diagram of ion transmembrane transport in Example 6 of the present invention; Fig.16 is an IV curve diagram of the MXene-CMC composite membrane in Example 6 of the present invention measured in neutral potassium chloride solutions of different concentrations; Fig.17 is a graph showing the change of conductivity and Debye length with KCl electrolyte concentration in Example 6 of the present invention; Fig.18 is an IT curve diagram measured under a cyclic bias voltage in Example 6 of the present invention; Fig.19 is an IV curve diagram measured under the electrolyte in Example 6 of the present invention; Fig. 20 It is a schematic diagram of a device for testing MXene-CMC composite membrane to obtain permeation energy in Example 6 of the present invention; Fig.21 Schematic diagram of short-circuit current and open-circuit voltage generated by MXene-CMC composite films of different thicknesses in Example 6 of the present invention; Fig. 22 is a power density diagram corresponding to MXene-CMC composite films of different thicknesses in Example 6 of the present invention; Fig.23 is a graph showing power density as a function of external load resistance in Example 6 of the present invention; Fig.24 is a current density diagram of the MXene-CMC composite membrane with the optimal thickness and blending ratio under different concentration gradients in Example 6 of the present invention; Fig.25 is a power density diagram of different measurement areas in Example 6 of the present invention; Fig.26 is a radial anion concentration distribution diagram of the nanochannel model at different channel radii in Example 6 of the present invention; Fig. 27 is a graph of power density and current density of osmotic energy extracted by the MXene-CMC composite membrane in Example 6 of the present invention as a function of load resistance; Fig.28 Schematic diagram comparing the salt difference power generation performance in Example 6 of the present invention with other works; Fig.29 is a distribution curve diagram of ion concentration along the axial position of the simulation channel under different surface charge densities in Example 6 of the present invention; Fig.30 is a schematic diagram of the effect of surface charge density on diffusion current and diffusion voltage in Example 6 of the present invention; Fig.31 Schematic diagram of the promotion effect between surface charge density and output power value in Example 6 of the present invention; Fig.32 is a schematic diagram showing the effect of the nanochannel diameter on the current and selectivity in Example 6 of the present invention; Fig.33 is a schematic diagram of the relationship between the nanochannel diameter and the output power in Example 6 of the present invention; Fig.34 Graphs of open circuit voltage and short circuit current at different pH gradients in Example 6 of the present invention; Fig.35Schematic diagram of the functional relationship between current density and load resistance in KCl and HCl electrolytes under the same concentration gradient in Example 6 of the present invention; Fig.36 Schematic diagram of the functional relationship between power density and load resistance in KCl and HCl electrolytes under the same concentration gradient in Example 6 of the present invention; Fig.37 Schematic diagram of the relationship between power density and efficiency as a function of pH gradient in Example 6 of the present invention; Fig.38 is a schematic diagram of the relationship between current density and load resistance at different pH gradients in Example 6 of the present invention; Fig.39 3 is a diagram of the maximum output power density of different pH gradients in Example 6 of the present invention. DETAILED DESCRIPTION
[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0020] Example 1 The preparation method of the MXene-CMC composite membrane for collecting salt difference energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing MXene solution; Step 2, preparing CMC solution; Step 3, placing the MXene solution prepared in step 1 into the CMC solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a suction filtration bottle, taking the mixed dispersion in the suction filtration bottle for vacuum-assisted filtration, and obtaining a polycarbonate membrane covered with a MXene-CMC composite membrane; Step 5: Peel off the MXene-CMC composite membrane from the polycarbonate membrane in the polycarbonate membrane covered with the MXene-CMC composite membrane, filter the water, and obtain a MXene-CMC composite membrane for collecting salt difference energy.
[0021] Example 2 The preparation method of the MXene-CMC composite membrane for collecting salt difference energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing MXene solution; The specific process is as follows: a certain amount of MXene dispersion is placed in a reactor and subjected to ultrasonic treatment to obtain a MXene solution; the concentration of the MXene solution is 1-5 mg / mL; the ultrasonic treatment time is 4-6 min; Step 2, preparing CMC solution; Step 3, placing the MXene solution prepared in step 1 into the CMC solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a suction filtration bottle, taking the mixed dispersion in the suction filtration bottle for vacuum-assisted filtration, and obtaining a polycarbonate membrane covered with a MXene-CMC composite membrane; Step 5: Peel off the MXene-CMC composite membrane from the polycarbonate membrane in the polycarbonate membrane covered with the MXene-CMC composite membrane, filter the water, and obtain a MXene-CMC composite membrane for collecting salt difference energy.
[0022] Example 3 The preparation method of the MXene-CMC composite membrane for collecting salt difference energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing MXene solution; The specific process is as follows: a certain amount of MXene dispersion is placed in a reactor and subjected to ultrasonic treatment to obtain a MXene solution; the concentration of the MXene solution is 1-5 mg / mL; the ultrasonic treatment time is 4-6 min; Step 2, preparing CMC solution; The specific process is: Step 2.1, take deionized water into the reactor and take a certain amount of CMC solid powder; Step 2.2, dissolving CMC solid powder in deionized water, and fully dissolving it by electromagnetic stirring to obtain a CMC solution; The concentration of CMC solution is 2-10 mg / mL; the electromagnetic stirring time is 24-36 h; Step 3, placing the MXene solution prepared in step 1 into the CMC solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a suction filtration bottle, taking the mixed dispersion in the suction filtration bottle for vacuum-assisted filtration, and obtaining a polycarbonate membrane covered with a MXene-CMC composite membrane; Step 5: Peel off the MXene-CMC composite membrane from the polycarbonate membrane in the polycarbonate membrane covered with the MXene-CMC composite membrane, filter the water, and obtain a MXene-CMC composite membrane for collecting salt difference energy.
[0023] Example 4 The preparation method of the MXene-CMC composite membrane for collecting salt difference energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing MXene solution; The specific process is as follows: a certain amount of MXene dispersion is placed in a reactor and subjected to ultrasonic treatment to obtain a MXene solution; the concentration of the MXene solution is 1-5 mg / mL; the ultrasonic treatment time is 4-6 min; Step 2, preparing CMC solution; The specific process is: Step 2.1, take deionized water into the reactor and take a certain amount of CMC solid powder; Step 2.2, dissolving CMC solid powder in deionized water, and fully dissolving it by electromagnetic stirring to obtain a CMC solution; The concentration of CMC solution is 2-10 mg / mL; the electromagnetic stirring time is 24-36 h; Step 3, placing the MXene solution prepared in step 1 into the CMC solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; The electromagnetic stirring adopts an electromagnetic stirrer, the rotation speed of the electromagnetic stirring is 1000-1500 rpm, and the time of the electromagnetic stirring is 12-24h.
[0024] Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a suction filtration bottle, taking the mixed dispersion in the suction filtration bottle for vacuum-assisted filtration, and obtaining a polycarbonate membrane covered with a MXene-CMC composite membrane; Step 5: Peel off the MXene-CMC composite membrane from the polycarbonate membrane in the polycarbonate membrane covered with the MXene-CMC composite membrane, filter the water, and obtain a MXene-CMC composite membrane for collecting salt difference energy.
[0025] Example 5 The preparation method of the MXene-CMC composite membrane for collecting salt difference energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing MXene solution; The specific process is as follows: a certain amount of MXene dispersion is placed in a reactor and subjected to ultrasonic treatment to obtain a MXene solution; the concentration of the MXene solution is 1-5 mg / mL; the ultrasonic treatment time is 4-6 min; Step 2, preparing CMC solution; The specific process is: Step 2.1, take deionized water into the reactor and take a certain amount of CMC solid powder; Step 2.2, dissolving CMC solid powder in deionized water, and fully dissolving it by electromagnetic stirring to obtain a CMC solution; The concentration of CMC solution is 2-10 mg / mL; the electromagnetic stirring time is 24-36 h; Step 3, placing the MXene solution prepared in step 1 into the CMC solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; The electromagnetic stirring adopts an electromagnetic stirrer, the rotation speed of the electromagnetic stirring is 1000-1500 rpm, and the time of the electromagnetic stirring is 12-24h.
[0026] Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a suction filtration bottle, taking the mixed dispersion in the suction filtration bottle for vacuum-assisted filtration, and obtaining a polycarbonate membrane covered with a MXene-CMC composite membrane; The time for vacuum-assisted filtration is 3-7 days; Step 5: Peel off the MXene-CMC composite membrane from the polycarbonate membrane in the polycarbonate membrane covered with the MXene-CMC composite membrane, filter the water, and obtain a MXene-CMC composite membrane for collecting salt difference energy.
[0027] Example 6 The preparation method of the MXene-CMC composite membrane for collecting salt difference energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing MXene solution; The specific process is as follows: a certain amount of MXene dispersion is placed in a reactor and subjected to ultrasonic treatment to obtain a MXene solution; the concentration of the MXene solution is 1-5 mg / mL; the ultrasonic treatment time is 4-6 min; Step 2, preparing CMC solution; The specific process is: Step 2.1, take deionized water into the reactor and take a certain amount of CMC solid powder; Step 2.2, dissolving CMC solid powder in deionized water, and fully dissolving it by electromagnetic stirring to obtain a CMC solution; The concentration of CMC solution is 2-10 mg / mL; the electromagnetic stirring time is 24-36 h; Step 3, placing the MXene solution prepared in step 1 into the CMC solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; The electromagnetic stirring adopts an electromagnetic stirrer, the speed of electromagnetic stirring is 1000-1500 rpm, and the time of electromagnetic stirring is 12-24h; like Figure 2 As shown in Figure 2, CMC molecular chains contain abundant -OH and -COOH groups, such as Figure 3 As shown, the CMC molecular chains and MXene nanosheets are fully cross-linked by stirring, and the obtained mixed dispersion exhibits an obvious Tyndall effect, indicating that MXene and CMC are uniformly dispersed in the aqueous phase; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a suction filtration bottle, taking the mixed dispersion in the suction filtration bottle for vacuum-assisted filtration, and obtaining a polycarbonate membrane covered with a MXene-CMC composite membrane; The time for vacuum-assisted filtration is 3-7 days; Step 5: Peel off the MXene-CMC composite film from the polycarbonate film covered with the MXene-CMC composite film, and filter out the water, such as Figure 4 , 5 As shown, a MXene-CMC composite membrane for salt difference energy collection is obtained; the composite membrane is named MXene-CMC-x, where x represents the mass ratio of CMC to MXene; Next, the dispersion and MXene-CMC composite membrane were characterized. Figure 6 As shown, the scanning electron microscope (SEM) surface image of the pure MXene film shows certain defects, such as Figure 7 As shown in the figure, the MXene-CMC composite film is relatively flat and smooth. Figure 8 , 9 As shown, the SEM cross-sectional image clearly shows that the layers of the composite film are thicker and stronger than those of the pure MXene film. The nanosheets are like thin "bricks" that become more stable through the pouring of "concrete" CMC. The EDS spectrum of the cross section shows that the main elements of MXene (C, O, F, Ti) are evenly distributed in the nanocomposite film. The transmission electron microscope (TEM) image characterizes that the size of the MXene nanosheets is about a few microns. The SEM image of CMC shows a very regular structure. Through tensile testing, we have proved that the composite film has better toughness and strength. The MXene-CMC-20 with a width of only 2mm can withstand a tensile force equivalent to the weight of an object of 1.6kg, such as Fig.10 As shown in the figure, the stress intensity reaches 135MPa. Fig.11 As shown in Figure 2, the MXene-CMC composite membrane also exhibits good hydrophilicity, which helps promote the transport of ions in the composite membrane. Due to the abundant hydrophilic groups in CMC, the contact angle gradually decreases with the increase of CMC content in the composite membrane, indicating that its hydrophilicity is enhanced. X-ray diffraction spectra (XRD) show that, as shown in Figure 2, Fig.12 As shown in Figure 2, the angle corresponding to the characteristic peak (002) of the composite membrane decreases. According to the Bragg law, the d spacing of the MXene and MXene-CMC composite membranes is calculated to be 1.45 nm and 1.50 nm, respectively, which indicates that the composite membrane can achieve a higher ion flux during ion transport. In addition, as Fig.13As shown in Figure 2, CMC exhibits good chargeability, with a zeta potential of up to -79.3 mV, significantly higher than -27.67 mV of MXene, which helps the composite membrane improve ion selectivity. The surface element state of the composite membrane was analyzed by X-ray photoelectron spectroscopy (XPS). The full spectrum of the MXene-CMC-20 composite membrane is shown in Figure 2. Fig.14 As shown, the binding energies of several characteristic elements are revealed. Further analysis of the C1s single spectrum shows that the composite film contains abundant oxygen-containing functional groups, thus exhibiting excellent charging properties.
[0028] The MXene-CMC composite membrane has excellent ion transport properties. The ion transport properties of the composite membrane were evaluated experimentally, where the CMC content of the tested composite membrane was about 95% (i.e., the mass ratio of CMC to MXene was 20), which was obtained by power density optimization. Fig.15 As shown in Figure 2, electrolyte solutions of the same concentration were added to the electrolytic cells on both sides of the composite membrane. Potassium chloride was chosen as the electrolyte solution because potassium ions and chloride ions have the same diffusion coefficient. The ion transport properties of the composite membrane were evaluated by ion current-voltage (IV) measurements. Fig.16 As shown in the figure, the IV curves at KCl electrolyte concentrations of 0.01, 0.1 and 1 M are shown, all of which show linear ohmic characteristics and the rectification effect is almost negligible, indicating that the structure of the composite membrane system is symmetrical. The conductivity measurement results reveal that the ion transport in the composite membrane channel is controlled by the surface charge. Fig.17 As shown in the figure, the transmembrane conductivity of ions shows two completely different patterns as the electrolyte concentration changes. At high concentrations, the conductivity is linearly related to the concentration, which is consistent with the bulk value. However, when the concentration is lower than 0.01 M, the ionic conductivity begins to deviate from the bulk value and gradually tends to a fixed value. This is because in the high concentration region, the double layer thickness (i.e. Fig.17 The Debye length λD in the channel is quite different from the channel size, so the conductivity is determined by the concentration. In the low concentration area, the double layer thickness is large and overlaps with the channel area, resulting in the ion transport being dominated by the surface charge. The Debye length (double layer thickness) is calculated according to the following formula: (1); Among them, ε, ε 0, R, T, nbulk, z and F represent the dielectric constant of water, the dielectric constant of vacuum, the universal gas constant, the absolute temperature, the solution concentration, the ion valence and the Faraday constant (107, 95, 79), respectively. As can be seen from formula (1), the Debye length is negatively correlated with the ion concentration in the solution. Compared with the MXene membrane, the MXene-CMC-20 composite membrane exhibits higher conductivity, especially at lower concentrations, the conductivity value is even one order of magnitude higher. This is mainly attributed to the incorporation of CMC, which widens the interlayer spacing of the two-dimensional membrane, thereby achieving more efficient ion transport. In order to evaluate the stability of the composite membrane during ion transport, the current time (IT) test was performed by alternating an external voltage of ±1 V. Each measurement cycle lasted 10 minutes, and a total of 15 cycles were performed. The test was carried out under acidic (pH=3), neutral (pH=7) and alkaline (pH=11) conditions, and the results showed that there was no obvious current decay within 9000 seconds, as shown in Figure 2. Fig.18 As shown, it shows that the composite membrane maintains good stability in three environments, laying a foundation for the subsequent measurement of energy conversion performance in acid-base environments. In addition, to further understand the confined ion transport, such as Fig.19 As shown in Figure 2, the chemical potential driven ion transport of several different chloride electrolytes under a 50-fold concentration gradient was measured. At zero bias voltage, the currents were all positive, which was determined by the preferential transport of cations by the MXene-CMC-20 composite membrane.
[0029] Next, the research on the salt difference energy conversion performance of MXene-CMC composite membrane was discussed. Fig. 20 As shown in the figure, the basic principle of salt difference energy conversion is demonstrated: driven by chemical potential (i.e., concentration gradient), ions selectively permeate through the composite membrane to form a potential difference, and then convert chemical energy into electrical energy through redox reactions on the electrodes. In order to explore the effect of CMC content on the salt difference energy conversion performance of the composite membrane, composite membranes with different CMC contents were prepared. With the increase of CMC content, the open circuit voltage (VOC) and short circuit current (ISC) both showed an upward trend at the beginning and then decreased. This phenomenon can be attributed to the increase of CMC, which increases the charge density and widens the nanomembrane channels, thereby enhancing the selectivity and ion flux. However, with the further increase of CMC content, the cross-linked CMC molecular chains reach saturation, and the excess CMC may block the membrane channels, resulting in a decrease in ion flux. When the mass ratio of MXene to CMC is 1:20, VOC and ISC achieve the best trade-off and reach the maximum output power density. After determining that MXene-CMC-20 is the composite membrane with the best performance, its osmotic energy conversion performance at different thicknesses was further studied. The measurement results under simulated seawater / river water conditions (i.e., NaCl solution with a concentration gradient of 50 times) show that when the membrane thickness is 60 μm, both the open circuit voltage and the short circuit current reach their maximum values, such as Fig.21 As shown in the figure, the maximum output power density of 12.3 W / m² was achieved. When the thickness is less than 60μm, the membrane structure is easily damaged, affecting the ion selectivity; when the thickness is greater than 60μm, the ion transmission path increases, reducing the transmission efficiency. In addition, the MXene-CMC composite membrane also exhibits excellent osmotic energy conversion performance under different concentration gradients. Fig. 22 It can be seen that with the increase of concentration gradient, the short-circuit current and open-circuit voltage both increase, reaching 40μA and 162mV respectively at a concentration gradient of 500 times (0.01M / 5M NaCl solution, i.e. simulated river water / salt lake). Fig.23 , 24 As shown in the figure, the output current density and power density are positively correlated with the concentration gradient. When the concentration gradient increases from 5 to 500, the power density increases from 1.81 W / m² to 53.78 W / m², which is mainly attributed to the increase in Gibbs free energy. In addition, the high ionic conductivity of the membrane helps to alleviate the concentration polarization problem, making it still advantageous in larger-scale applications. Fig.25 As shown in the figure, under a 50-fold concentration gradient, when the cross-sectional area of ion transmission increases to 1.00 mm² and 2.25 mm² respectively, the maximum output power density can still reach 0.56 W / m² and 0.26 W / m².
[0030] Due to the cation selectivity of the composite membrane, several major cations in seawater were selected for the salt difference energy conversion performance test. The anions were all Cl - The results show that in K + and Li + In solution, the power density is as high as 13.97 W / m² and 10.02 W / m² respectively, while in the case of divalent ion Mg² + and Ca² + The permeability of different ions is mainly affected by the difference in their diffusion coefficients. Although the diffusion coefficient of calcium ions is slightly larger than that of magnesium ions, the radius of calcium ions is about 50% larger than that of magnesium ions. Therefore, when passing through nanochannels, they are more susceptible to the force of negatively charged functional groups, causing them to stay in the membrane channels. Studies have shown that the cross-linking effect of calcium ions can enhance the mechanical strength of the membrane, while the cross-linking effect of magnesium ions is weaker, so the diffusion of calcium ions in the membrane is more restricted. Although in Ca² + The power density measured in solution is the lowest, but the content in real seawater is also the lowest, only Mg² + About 20% of Na + To further verify the energy conversion performance of the membrane system in the natural environment, we used natural seawater (seawater samples were taken from the South China Sea) to replace the electrolyte solution on the high concentration side for measurement. Fig.26As shown in the figure, in the natural seawater / simulated river water system, the output power density reached 17.10 W / m², which is higher than the value measured under a 50-fold NaCl gradient. This may be because the total cation concentration in natural seawater is greater than 0.5 M, and the composite membrane has good selective transmission for several major cations in seawater. Fig. 27 As shown, by comparing with some previous works, under a similar measurement system, the output power density of the membrane system shows significant advantages.
[0031] In order to further clarify the mechanism of high performance of MXene-CMC composite membrane, the continuum model of Poisson-Nernst-Planck equation was used for simulation. Fig.28 As shown in Figure 1, the ion transport path is simplified to a single negatively charged nanochannel. Fig.29 As shown in the figure, the simulation results intuitively reveal the concentration polarization phenomenon: at the junction of the low-concentration side and the nanochannel, an ion-enriched area appears. The solution concentration in this area is significantly higher than the concentration in the pool, resulting in the actual concentration difference being smaller than the ideal concentration difference. On the contrary, at the junction of the high-concentration side and the nanochannel, there is an ion dissipation area. Since the high concentration reduces the thickness of the double electric layer and has a weaker effect on ions, the difference between the ion concentration in the dissipation zone and the ion concentration in the bulk phase is not obvious.
[0032] Subsequently, the effect of surface charge density on the ion permeation power generation performance of nanochannels was studied. Fig.30 As shown in Figure 2, as the surface charge density increases, the nanochannel attracts more ions with opposite electrical properties, thereby increasing the diffusion current and diffusion voltage, as shown in Figure 2. Fig.31 As shown in Figure 2, the penetration power of the nanochannel is significantly improved. Another key factor in the ion transport performance of the nanochannel is the channel diameter. Fig.32 As shown in Figure 2, as the diameter of the nanochannel increases, the double layer effect gradually weakens. Although the ion selectivity decreases slightly, the ion flux increases significantly, thereby increasing the output current. Fig.33 As shown, the permeation power of the nanochannel is improved. These results explain the excellent performance of the MXene-CMC composite membrane in osmotic power generation. In this application, compared with the pure MXene membrane, the MXene-CMC composite membrane exhibits stronger charge and larger interlayer spacing, successfully achieving two important conditions for improving the output power of the nanochannel, so its osmotic energy conversion performance is significantly better than that of the pure MXene membrane.
[0033] In addition to the abundant osmotic energy generated by the confluence of seawater and river water, acid and alkaline wastewater generated by industrial activities also contains considerable osmotic energy. This resource has great potential and deserves to be explored, extracted and used efficiently. Compared with other ions, such as the main ions in seawater, hydrogen ions and hydroxide ions in acids and alkalis have special properties. The two will undergo a neutralization reaction "H + +OH - →H 2 O", merged into part of the solvent, causing the hydrogen ions on one side of the membrane to selectively permeate to the other side of the composite membrane, such as Fig.34 As shown, it is rapidly consumed by hydroxide ions, thereby making H + can migrate continuously. This process almost eliminates the polarization effect of hydrogen ions on the opposite side and significantly increases the net concentration gradient. This is different from other ions, where the actual concentration gradient is less than the set concentration gradient due to the enrichment effect of ions on the low-concentration side around the membrane. In addition, the diffusion coefficient of hydrogen ions is much larger than that of other ions. Therefore, under the same concentration gradient conditions (1 M-0.001 M), the permeation current density and power density generated by HCl are significantly higher than those of KCl. It has been determined in previous studies that under the same concentration gradient, due to the K + With a high diffusion coefficient, KCl can generate the largest salt difference power generation, such as Fig.35 , 36 As shown, the power of HCl is nearly 4 times that of HCl. In order to better understand the difference in energy conversion performance under the two ion conditions, we calculated the ion mobility of the two. The mobility of ions can be calculated using the Einstein relationship136: (2); in μ is the ion mobility, Di is the ion diffusion coefficient, q is the charge of the ion (C), k B is the Boltzmann constant, T is the temperature (K). + and K + The diffusion coefficients are 9.311×10 -5 cm 2 s -1 and 1.957×10 -5 cm 2 s -1 , so according to equation (2) we can calculate H + and K + The mobility of μ 25℃ (H + )=3.623×10 -7 m2 V −1 s −1 and μ 25℃ (K + )=7.614×10-8m 2 V −1 s −1 , which is consistent with the existing value. + The mobility ratio K + It is nearly an order of magnitude higher, which means that H + The flux is much greater than K + , thus showing higher power density.
[0034] Subsequently, the energy conversion performance of the composite membrane under different pH gradients was studied. In the experiment, since the electrode used was an AgCl electrode, the acid and alkaline solutions of each pH contained 0.01 M NaCl as a supporting solution to prevent the electrode from reacting and being damaged under alkaline conditions. In the several different pH gradients studied, such as Fig.37 As shown in the figure, the open circuit voltage (VOC) is as high as 256 mV and the short circuit current (ISC) is as high as 126 μA. Fig.38 As shown in Figure 2, as the pH gradient increases, the load resistance corresponding to the maximum output power density gradually decreases. This is mainly because the increase in concentration gradient and the neutralization reaction promote the transmission of ions, thereby increasing the ionic conductivity of the membrane. Fig.39 As shown in the figure, when the pH gradient is 0-3, the output power density reaches 62.47 W / m², which is almost three times that of the ANF membrane under the same conditions and ten times that of the pure MXene membrane. When the pH gradient is 0-14, the output power density is as high as about 200 W / m², which is much larger than the value under the pure HCl concentration gradient. This is due to the neutralization reaction of H + In summary, the success of achieving high-performance osmotic energy conversion under acid-base conditions depends not only on the superior performance of the composite membrane itself, but more importantly on the high mobility characteristics of hydrogen ions. + With OH - The unique properties of the neutralization reaction between ions effectively eliminate the enrichment of ions, which is another key factor in promoting high-performance osmotic energy conversion. Neutralization reaction is also a necessary process for acid-base wastewater treatment, so extracting osmotic energy from acids and bases here can be said to kill two birds with one stone, that is, it realizes the utilization and treatment of wastewater at the same time.
[0035] We simply prepared a highly economical and high-performance two-dimensional composite membrane by vacuum filtration. In the natural seawater / simulated river water system, the membrane showed excellent performance, with a power density of 17.10 W / m², far exceeding the commercial benchmark value. Under the condition of 500 times concentration gradient (simulated salt lake / river water), a high power density of 53.75 W / m² was achieved for salt difference energy collection. When it was applied to the salt difference energy collection of simulated acid-base wastewater, the power density was as high as about 200 W / m², so the composite membrane has a wider range of applications. Another major advantage of the prepared composite membrane is its low cost. Although MXene materials are expensive, their content in the composite membrane is extremely small; and CMC, as the main body of the composite membrane, is not only low in price and easy to extract and prepare, but its abundant reserves in nature make it an excellent environmentally friendly material. The composite membrane synthesized with this environmentally friendly material realizes the efficient "utilization-treatment" integration of acid-base wastewater, not only realizing high power density energy collection, but also effectively treating wastewater. This application is an important step forward in the extraction of osmotic energy in ion gradients and the treatment and utilization of acid and alkaline wastewater.
Claims
1. A method for preparing a MXene-CMC composite membrane for collecting salinity difference energy, characterized in that: The specific steps include: Step 1, preparing MXene solution; Step 2, preparing CMC solution; Step 3, placing the MXene solution prepared in step 1 into the CMC solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a suction filtration bottle, taking the mixed dispersion in the suction filtration bottle for vacuum-assisted filtration, and obtaining a polycarbonate membrane covered with a MXene-CMC composite membrane; Step 5: Peel off the MXene-CMC composite membrane from the polycarbonate membrane in the polycarbonate membrane covered with the MXene-CMC composite membrane, filter the water, and obtain a MXene-CMC composite membrane for collecting salt difference energy.
2. The method for preparing a MXene-CMC composite membrane for salinity energy collection according to claim 1, characterized in that: The specific process of step 1 is: taking a certain amount of MXene dispersion into a reactor, performing ultrasonic treatment, and obtaining a MXene solution.
3. The method for preparing a MXene-CMC composite membrane for salinity energy collection according to claim 2, characterized in that: The concentration of the MXene solution is 1-5 mg / mL.
4. The method for preparing a MXene-CMC composite membrane for salinity energy collection according to claim 2, characterized in that: The ultrasonic treatment time is 4-6 minutes.
5. The method for preparing a MXene-CMC composite membrane for salinity energy collection according to claim 1, characterized in that: The specific process of step 2 is: Step 2.1, take deionized water into the reactor and take a certain amount of CMC solid powder; Step 2.2: Dissolve CMC solid powder in deionized water and fully dissolve it by electromagnetic stirring to obtain a CMC solution.
6. The method for preparing a MXene-CMC composite membrane for salinity energy collection according to claim 5, characterized in that: The concentration of the CMC solution is 2-10 mg / mL.
7. The method for preparing a MXene-CMC composite membrane for salinity energy collection according to claim 5, characterized in that: The electromagnetic stirring time is 24-36h.
8. The method for preparing a MXene-CMC composite membrane for salinity energy collection according to claim 1, characterized in that: The electromagnetic stirring in step 3 uses an electromagnetic stirrer, the rotation speed of the electromagnetic stirring is 1000-1500 rpm, and the time of the electromagnetic stirring is 12-24h.
9. The method for preparing a MXene-CMC composite membrane for salinity energy collection according to claim 1, characterized in that: The vacuum-assisted filtration time in step 4 is 3-7 days.
10. MXene-CMC composite membrane for salinity energy collection, characterized in that: The MXene-CMC composite membrane for salt difference energy collection is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
CMC-coated Ti3C2Tx layered composite film as well as preparation method and application thereof
CN115253721A
Preparation method and application of MXene / carboxymethyl xylan nanofluidic membrane for salinity difference energy conversion
CN115772279A